1991
DOI: 10.5465/256404
|View full text |Cite
|
Sign up to set email alerts
|

People and Organizational Culture: A Profile Comparison Approach to Assessing Person-Organization Fit

Abstract: This article brings together three current themes in organizational behavior: (1) a renewed interest in assessing person-situation interactional constructs, (2) the quantitative assessment of organizational culture, and (3) the application of "Q-sort," or template-matching, approaches to assessing person-situation interactions. Using longitudinal data from accountants and M.B.A. students and cross-sectional data from employees of government agencies and public accounting firms, we developed and validated an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
1,174
2
50

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 950 publications
(1,268 citation statements)
references
References 67 publications
(50 reference statements)
42
1,174
2
50
Order By: Relevance
“…Mitchell et al (2001) argue that the better the fit, the higher the likelihood that an employee will feel professionally and personally tied to (or embedded in) the organization. People who do not fit tend to leave the organization rapidly (cf: O'Reilly et al, 1991). Having a good fit, of course does not guarantee better employee or work unit performance.…”
Section: Discussionmentioning
confidence: 99%
“…Mitchell et al (2001) argue that the better the fit, the higher the likelihood that an employee will feel professionally and personally tied to (or embedded in) the organization. People who do not fit tend to leave the organization rapidly (cf: O'Reilly et al, 1991). Having a good fit, of course does not guarantee better employee or work unit performance.…”
Section: Discussionmentioning
confidence: 99%
“…Measures of variability of behavior are as readily available as measures of means and should also be reported in cross-cultural studies. The notion that organizational cultures differ on the extent to which they emphasize rules and predictability versus flexibility and experimentation has a long history in the organizational sciences (Litwin & Stringer, 1968;O'Reilly, Chatman, & Caldwell, 1991;O'Reilly & Chatman, 1996;Quinn, 1988;Rousseau, 1990 shown that flexibility and experimentation versus rule orientation is a central dimension of organizational culture (Dastmalchian, Lee, & Ng, 2000;Hofstede, Neuijen, Ohayv, & Sanders, 1990;Verberg, Drenth, Koopman, van Muijen, and Wang, 1999).…”
Section: Societal Tightness-looseness and Cross-level Effects On Indimentioning
confidence: 99%
“…The notion that individuals in tight societies are acutely affected by a lack of fit can be tested with multilevel modeling techniques wherein societal tightness-looseness moderates the relationship between person-organization fit and/or person-team fit and satisfaction, stress, and turnover intentions (e.g., O'Reilly et al, 1991).…”
Section: Research Implications Of Propositions 8-10mentioning
confidence: 99%
“…Researchers are particularly interested in determining which type of culture stimulates or hampers innovation. Even though many types of organizational culture have been established since this concept first appeared in the literature (Frohman 1998a, b;Schein 1996a, b;O'Relly et al 1991), the most widespread and used in many empirical studies is Cameron and Quinn's model (1999), the competing values framework (CVF), from which four cultures-adhocracy, clan, market and hierarchy-emerge. The clan culture is based on flexibility and internal focus.…”
Section: Organisational Culture and Innovativenessmentioning
confidence: 99%